Falling with Style: Bats Perform Complex Aerial Rotations by Adjusting Wing Inertia - Bergou, Attila J.; Swartz, Sharon M.; Vejdani, Hamid; Riskin, Daniel K.; Reimnitz, Lauren; Taubin, Gabriel; Breuer, Kenneth S. (PLOS Biology, 2015)
How do bats turn in mid-air in order to land or recover from a fall? This study compares numerical simulation with high-speed video, demonstrating that bats are able to reorient solely through inertial forces by maneuvering their heavy wings.